Optimisation Of Palm Oil Degumming Process Towards Refined Bleached Deodorised Palm Oil Safety And Quality - Ismail, Mohammad Saiful Nidzam (2022)
Physical refining is the most common refining route practiced in Malaysia palm oil industries which involves the processing stages of degumming, bleaching and deodorisation. However, degumming is one of the crucial steps of the crude palm oil refinery process since the performance of the degumming process tremendously affects the later stages of refining processes and finally affect the produced palm oil. Besides, the degumming process of crude palm oil is one of the significant contributors to the total operating cost of the palm oil refinery process due to the cost of the degumming agent. In the present study, the influence of the phosphoric acid degumming process was determined on the formation of 3-monochloropropane-1,2- diol esters (3-MCPD) and glycidyl esters (GE) in refined, bleached, and deodorised palm oil (RBDPO).